MURDER Using Learning to Improve Understanding Motivation and Learning Ability - Emi Lilawati; Dian Kusuma Wardani; Alfi Qurrota Aini (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to determine the influence of Murder (cooperative) learning on learning outcomes reviewed from students' learning understanding and motivation. This study uses quantitative method with a type of questionnaire involving students of grade X SMK PGRI 2 Jombang with a population of 322 students, with a sample of 76 students randomly selected, data retrieval using questionnaires as data collection to find out how MURDER learning can motivate students. The results showed that the validity test results that have been conducted in this study showed that all questionnaire items (X1) were valid with a total score of Sig. greater than 0.227 and person correlation was positive. The results of the reliability test were then compared with the table r in this study N=76 and dk = 76 – 2 =74 with a significant level of 5% so that the table r value = 0.227. If r calculates ≥ r table then reliable question items, From the SPSS output results it appears that the significant value in the questionnaire 0.002 > .01 so it can be said that the data spread following the spread normal, and Hypothesis Test in this study shows that Murder learning has an effect on student learning.